Laboratory investigation of fatigue parameters characteristics of aging asphalt mixtures: A dissipated energy approach. (10th January 2020) - Lv, Songtao; Peng, Xinghai; Liu, Chaochao; Ge, Dongdong; Tang, Minmin; Zheng, Jianlong
Highlights: The variation patterns of fatigue parameters with aging degree were established. Sensitivity analysis of fatigue parameters for aging asphalt mixture was carried out. Statistical models of the relation between PV and fatigue life have been derived. Abstract: The objective of this paper is to reveal the effects of aging on the fatigue performance of asphalt mixture based on variation patterns of fatigue parameters with aging degrees. Specimens with different aging degrees were prepared by modified SHRP's Long-Term-Oven Aging (LTOA) test method, in which five different aging durations, included 0, 1, 3, 5, 7 days, were adopted to substitute the fixed 5 days. The fatigue parameters, including stiffness modulus, fatigue life, phase angle, Plateau Value (PV), and cumulative dissipation energy of specimens with different aging degrees under different stress ratios were obtained by the tensile fatigue test. The relationship of fatigue parameters with aging degrees and stress ratios were established. It could be observed from the results that the aging degree and stress ratio had dramatic influences on the fatigue performance of asphalt mixture. Sensitivity analysis showed that aging had the most significant effect on the initial stiffness modulus of asphalt mixture, and should be used as a control index in fatigue design. Statistical models of the relation between (PV) and fatigue life ( N f ) established by the Rate of Dissipated Energy Change (RDEC) approach has an effective correlation. The Plateau Value model eliminated the effects of aging degrees and reflected the uniqueness of material parameters. Also, it could provide novel ideas for effective prediction of the fatigue life of asphalt mixtures with different aging degrees based on plateau value.